Avant-Garde and Liberation : Contemporary Art and Decolonial Modernism - Kravagna, Christian; Gebetsroither, Ines (Wien ; Cologne : mumok - Museum moderner Kunst Stiftung Ludwig Wien : Verlag der Buchhandlung Walther und Franz König, 2024)
Kleyebe Abonnenc, Mathieu ; Ba, Omar ; Bailey, Radcliffe ; Barrada, Yto ; Bourouissa, Mohamed ; Brackens, Diedrick ; Attukwei Clottey, Serge ; Cordova, William ; Dodiya, Atul ; Gabris, Robert ; Gronostay, Jojo ; Hewitt, Leslie ; Issa, Iman ; Jembere, Janine ; Kaersenhout, Patricia ; Kazeem-Kamiński, Belinda ; Leonard, Zoe ; Meessen, Vincent ; The Otolith Group ; Pecou, Fahamu ; Smith, Cauleen ; Sulter, Maud ; Sundaram, Vivan ; Takadiwa, Moffat
Avant-Garde and Liberation. Contemporary Art and Decolonial Modernism, mumok - Museum moderner Kunst Stiftung Ludwig Wien, Wien, June 7 to September 22, 2024
boek